Effect of Nano Material Ratio on Some Surface Properties of Wood Polymer Nanocomposites - Kaymakcı, Alperen (Zenodo, 2024)
Organic materials such as agricultural wastes and forest industry wastes can be successfully used as organic fillers in polymer composite production. Wood polymer composites are generally defined as a group of materials formed by combining two or more materials in a polymer matrix. As a result of their studies to improve the performance level, researchers have determined that this situation can be eliminated by using nano materials as reinforcing reinforcement material in wood plastic composite structure. The aim of this study is to determine some surface properties of wood plastic nanocomposites reinforced with nano-sized SiO2. Four wood polymer nanocomposites containing nano SiO2 at four different ratios were produced for the purpose. Surface roughness and hardness values of the wood polymer composites were determined. It was determined that the surface roughness values of wood polymer nanocomposite groups decreased as the SiO2 nano material ratio increased. On the other hand, when the data on pencil hardness values were analyzed, it was determined that the pencil hardness values of wood polymer nanocomposite groups increased as the SiO2 nanomaterial ratio increased.